TERMINOLOGY IN ENGLISH: BORROWING AND ASSIMILATION - Koshanova Saxibjamal Baxitbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Summary: This article focuses on examining and scientifically describing the semantic characteristics of English loanwords in contemporary Russian. The borrowed lexemes that have recently entered the Russian language are categorized into three main groups based on their level of semantic assimilation. By analyzing journalistic literature, online publications, explanatory dictionaries, foreign dictionaries, and etymological dictionaries, the article attempts to analyze the processes of reception and adaptation of English terminology.